2017
DOI: 10.1080/08958378.2017.1384085
|View full text |Cite
|
Sign up to set email alerts
|

Association of waterpipe smoking with myocardial infarction and determinants of metabolic syndrome among catheterized patients

Abstract: The study provides yet another evidence for the adverse cardiovascular effects of waterpipe smoking on a clinical level. The harmful effects of waterpipe smoking should be underscored by health care professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…The harmful effects of WPS are reflected by the increased CAC score (Chami et al, 2019) and the acute (Alomari et al, 2014;Rezk-Hanna et al, 2019;Wolfram et al, 2003) and long-term (Al-Numair et al, 2007;Diab et al, 2015;Ghasemi et al, 2010;Koubaa et al, 2015a;Selim et al, 2013a) endothelial dysfunction, which were established among waterpipe smokers, providing clinical evidence for the potential contribution of WPS to vascular disease. Our findings on WPS effects on cardiovascular system explain and support results of studies which reported a significant correlation between WPS and each of incidence (Al-Amri et al, 2019;Islami et al, 2013;Jabbour et al, 2003;Platt et al, 2017), worse clinical outcomes (Al Suwaidi et al, 2012) and estimated prognoses (Selim et al, 2013b;Sibai et al, 2014) of CVD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The harmful effects of WPS are reflected by the increased CAC score (Chami et al, 2019) and the acute (Alomari et al, 2014;Rezk-Hanna et al, 2019;Wolfram et al, 2003) and long-term (Al-Numair et al, 2007;Diab et al, 2015;Ghasemi et al, 2010;Koubaa et al, 2015a;Selim et al, 2013a) endothelial dysfunction, which were established among waterpipe smokers, providing clinical evidence for the potential contribution of WPS to vascular disease. Our findings on WPS effects on cardiovascular system explain and support results of studies which reported a significant correlation between WPS and each of incidence (Al-Amri et al, 2019;Islami et al, 2013;Jabbour et al, 2003;Platt et al, 2017), worse clinical outcomes (Al Suwaidi et al, 2012) and estimated prognoses (Selim et al, 2013b;Sibai et al, 2014) of CVD.…”
Section: Discussionsupporting
confidence: 90%
“…A significant correlation between WPS and the incidence of CVD was reported in four out of seven differently designed stud-ies (Al-Amri et al, 2019;Al Suwaidi et al, 2012;Chami et al, 2019;Islami et al, 2013;Jabbour et al, 2003;Platt et al, 2017;Saffar Soflaei et al, 2018). In a large population-based cohort study with 50045 participants (Islami et al, 2013) heart disease correlated to the consumption of > 180 waterpipe-year (OR: 3.75; 95% CI: 1.52 to 9.22).…”
Section: Cardiovascular Disease 34291 Incidence Of Cardiovascularmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, dyslipidemia was associated with narghile use. In a Lebanon study performed on patients undergoing cardiac catheterization, Platt et al (2017) noted that MI was significantly and independently associated with narghile use (OR: 1.33), which is lower than that for cigarette consumption (OR:1.87). Moreover, only DM presented significant association with narghile use among MI enrollees (OR: 1.66).…”
Section: Discussionmentioning
confidence: 93%
“…Water pipe (shisha) produces similar risks for bystanders as tobacco cigarettes, but concentrations of carbon monoxide and heavy metals are higher in SHS from shisha. Depending on intensity and duration of passive exposure similar CVDs could develop as proven for active consumption, while acute cardiovascular effects on risk groups are expected mainly from fine particulate matter, carbon monoxide and nicotine [73][74][75]. Animal experiments showed hypercoagulability, inflammation, as well as systemic and cardiac oxidative stress [76].…”
Section: Cardiovascular Risks Of Passive Exposure To Emissions Of Watmentioning
confidence: 99%